2014 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--23228
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Benefits of the Flipped Classroom in the Context of Sustainable Engineering

Abstract: is a faculty member in the Penn State Department of Architectural Engineering. His fields of expertise include education for sustainability, sustainable building methods, renewable energy deployment, and sustainable housing design. Dr Riley directed Penn State's Center for Sustainability (now Sustainability Institute) from 2005 to 2013. He currently serves as the Senior Resident Scholar and Reinvention Fund Program Manager for the Institute. Dr. Riley also leads multiple DOE funded energy centers, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Among the popular flipped classroom methods, experimental evidence from most researchers has shown that active autonomous learning can effectively improve learning performance [54]. When conducting courses in the form of flipped classrooms, instructional videos can help learners to acquire knowledge and skills.…”
Section: Assisting Students With Solving Practical Problemsmentioning
confidence: 99%
“…Among the popular flipped classroom methods, experimental evidence from most researchers has shown that active autonomous learning can effectively improve learning performance [54]. When conducting courses in the form of flipped classrooms, instructional videos can help learners to acquire knowledge and skills.…”
Section: Assisting Students With Solving Practical Problemsmentioning
confidence: 99%
“…Frontal lectures are necessary to teach students in situation where they hold no prior knowledge in a particular field. However, such setup has demonstrated shortcomings that could be impacting students' education, their ability to retain, analyze, and apply knowledge and the development of skills important for their careers outside of academia (Hattie 2008, Marks et al 2014, Schwerdt and Wuppermann 2011. Some of the noted limitations include the small amount of teacher-student interaction, the rigid pace of the lecture, and the fact that lectures only take advantage of one information delivery method (Goodwin 2013, Toto andNguyen 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we report an experience on the implementation of the FC method in an undergraduate course in renewable energies mediated by social platforms. The organization of such courses in universities responds to an increasing interest on this topic among students, and to meet industry requests of specialized workers (Marks et al 2014, Tomas et al 2019, Yasnin et al 2017. To make courses more appealing and to present the most up-to-date renewable energy issues, lecturers started to implement a series of information technology-based innovations in learning (Ebers Broughel et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although flipped classroom models have existed for many years, they have only recently begun to grow in popularity in engineering. Various studies have shown flipped classes to be particularly effective in engineering (Ankeny and Krause, 2014;Marks, 2014;Xiaobin et al 2015). More specifically, studies have been conducted on flipping engineering economics courses Brill, 2013, Lavelle, Stimpson andBrill, 2015).…”
Section: Active Learning: the Flipped Classroommentioning
confidence: 99%